Time to strategy failure and treatment beyond progression in pretreated metastatic renal cell carcinoma patients receiving nivolumab: post-hoc analysis of the Meet-URO 15 study - Murianni, Veronica; Signori, Alessio; Buti, Sebastiano; Rebuzzi, Sara Elena; Bimbatti, Davide; De Giorgi, Ugo; Chiellino, Silvia; Galli, Luca; Zucali, Paolo Andrea; Masini, Cristina; Naglieri, Emanuele; Procopio, Giuseppe; et al. (Frontiers in Oncology, 2024)
Background: Immunotherapies exhibit peculiar cancer response patterns in contrast to chemotherapy and targeted therapy. Some patients experience disease response after initial progression or durable responses after treatment interruption. In clinical practice, immune checkpoint inhibitors may be continued after radiological progression if clinical benefit is observed. As a result, estimating progression-free survival (PFS) based on the first disease progression may not accurately reflect the actual benefit of immunotherapy. Methods: The Meet-URO 15 study was a multicenter retrospective analysis of 571 pretreated metastatic renal cell carcinoma (mRCC) patients receiving nivolumab. Time to strategy failure (TSF) was defined as the interval from the start of immunotherapy to definitive disease progression or death. This post-hoc analysis compared TSF to PFS and assess the response and survival outcomes between patients treatated beyond progression (TBP) and non-TBP. Moreover, we evaluated the prognostic accuracy of the Meet-URO score versus the International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) score based on TSF and PFS. Results: Overall, 571 mRCC patients were included in the analysis. Median TSF was 8.6 months (95% CI: 7.0 -10.1), while mPFS was 7.0 months (95% CI: 5.7 -8.5). TBP patients (N = 93) had significantly longer TSF (16.3 vs 5.5 months; p < 0.001) and overall survival (OS) (34.8 vs 17.9 months; p < 0.001) but similar PFS compared to non-TBP patients. In TBP patients, a median delay of 9.6 months (range: 6.7-16.3) from the first to the definitive disease progression was observed, whereas non-TBP patients had overlapped median TSF and PFS (5.5 months). Moreover, TBP patients had a trend toward a higher overall response rate (33.3% vs 24.3%; p = 0.075) and disease control rate (61.3% vs 55.5%; p = 0.31). Finally, in the whole population the Meet-URO score outperformed the IMDC score in predicting both TSF (c-index: 0.63 vs 0.59) and PFS (0.62 vs 0.59). Conclusions: We found a 2-month difference between mTSF and mPFS in mRCC patients receiving nivolumab. However, TBP patients had better outcomes, including significantly longer TSF and OS than non-TBP patients. The Meet-URO score is a reliable predictor of TSF and PFS.